Understanding the Matrix: The Role of Extracellular DNA in Oral Biofilms - Serrage, Hannah J.; Jepson, Mark A.; Rostami, Nadia; Jakubovics, Nicholas S.; Nobbs, Angela H. (Frontiers in Oral Health, 2021)
Dental plaque is the key aetiological agent in caries formation and the development of the prevalent chronic oral inflammatory disease, periodontitis. The dental plaque biofilm is comprised of a diverse range of microbial species encased within a rich extracellular matrix, of which extracellular DNA (eDNA) has been identified as an important component. The molecular mechanisms of eDNA release and the structure of eDNA have yet to be fully characterised. Nonetheless, key functions that have been proposed for eDNA include maintaining biofilm structural integrity, initiating adhesion to dental surfaces, acting as a nutrient source and facilitating horizontal gene transfer. Thus, eDNA is a potential therapeutic target for the management of oral disease-associated biofilm. This review aims to summarise advances in the understanding of the mechanisms of eDNA release from oral microorganisms and in the methods of eDNA detection and quantification within oral biofilms.